2015
DOI: 10.1093/annonc/mdv139
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization by BRAF inhibitor therapy—mechanism and frequency of toxicity in melanoma patients

Abstract: Radiotherapy with concomitant BRAF inhibitor therapy is feasible with an acceptable increase in toxicity. Vemurafenib is a more potent radiosensitizer than dabrafenib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 27 publications
0
100
0
3
Order By: Relevance
“…30 In a nonrandomized comparison with patients receiving vemurafenib, vemurafenib was associated with significantly higher levels of acute radiodermatitis than dabrafenib (40% vs 26%, P = 0.07). There was no radiodermatitis > grade 1 seen with SRS.…”
Section: Radiotherapymentioning
confidence: 91%
“…30 In a nonrandomized comparison with patients receiving vemurafenib, vemurafenib was associated with significantly higher levels of acute radiodermatitis than dabrafenib (40% vs 26%, P = 0.07). There was no radiodermatitis > grade 1 seen with SRS.…”
Section: Radiotherapymentioning
confidence: 91%
“…The development of BRAF inhibitors (i.e., vemurafenib, dabrafenib) has led to a significant improvement in the overall survival among patients who harbor this mutation (125,130,131). Interestingly, BRAF inhibitor was found to have radio sensitization effect (132,133). However, the radiosensitization effect of BRAF inhibitor also increased the risk of skin toxicities with radiation (133)(134)(135)(136).…”
Section: Rt With Concomitant Agentsmentioning
confidence: 99%
“…Interestingly, BRAF inhibitor was found to have radio sensitization effect (132,133). However, the radiosensitization effect of BRAF inhibitor also increased the risk of skin toxicities with radiation (133)(134)(135)(136). Due to the minimum skin dose from SRS, several studies that evaluated BRAF inhibitor with SRS for patients with brain metastases reported favorable outcome (137)(138)(139).…”
Section: Rt With Concomitant Agentsmentioning
confidence: 99%
“…Vemurafenib kezelés mellett gyakran észlelünk fotoszenzitivitást. Sugárkezelt bőrterület vagy belső szerv súlyos akut gyulladásos reakciója jelentkezhet a gyógyszerszedés alatt az irradiációval egyidejűleg vagy röviddel utána (radioszenzitizáció), de akár jóval később (átlag 1 hónappal) a sugárkezelés befejezése után ("radiation recall") (21,22). A BRAF inhibitorok specifikus mellékhatásaként benignus (pl.…”
Section: Braf Inhibitor Kezelés (Hatékonyság Mellékhatás)unclassified